Elucidating the context for implementing nonpharmacologic care for neonatal opioid withdrawal syndrome: a qualitative study of perinatal nurses - Clayton J. Shuman; Roxanne Wilson; Katherine VanAntwerp; Mikayla Morgan; Ashley Weber (BMC, 2021)
Abstract Background Up to 95% of neonates exposed to opioids in utero experience neonatal opioid withdrawal syndrome at birth. Nonpharmacologic approaches (e.g., breastfeeding; rooming-in; skin-to-skin care) are evidence-based and should be implemented. These approaches, especially breastfeeding, rely on engagement of the neonates' mothers to help deliver them. However, little is known about the structural and social dynamic context barriers and facilitators to implementing maternal-delivered nonpharmacologic care. Methods Using a qualitative descriptive design, perinatal nurses from a Midwest United States hospital family birthing center, neonatal intensive care unit, and inpatient pediatric unit were interviewed. These units were involved in caring for mothers and neonates affected by opioid use. Telephone interviews followed a semi-structured interview guide developed for this study, were audio-recorded, and lasted about 30-60 min. Interviews were transcribed verbatim and independently analyzed by five investigators using the constant comparative method. Themes were discussed until reaching consensus and subsequently mapped to a conceptual model adapted for this study. Results Twenty-one nurses participated in this study (family birth center, n = 9; neonatal intensive care, n = 6; pediatrics, n = 6). Analysis resulted in four major themes: 1) Lack of education and resources provided to staff and mothers; 2) Importance of interdisciplinary and intradisciplinary care coordination; 3) Flexibility in nurse staffing models for neonatal opioid withdrawal syndrome; and 4) Unit architecture and layout affects maternal involvement. Minor themes supported each of the four major themes. All themes mapped to the conceptual model. Conclusions This study provides a more comprehensive understanding of the barriers and facilitators affecting implementation of maternal involvement in nonpharmacologic care of newborns with neonatal opioid withdrawal syndrome. Future efforts implementing nonpharmacologic approaches must consider the context factors affecting implementation, including structural and social factors within the units, hospital, and broader community.